2015
DOI: 10.1007/s11524-015-0015-8
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Predictors of Event-Level Associations between Alcohol Consumption and Sexual Behavior

Abstract: Alcohol consumption is associated with sexual behavior and outcomes, though research indicates a variety of moderating factors, including demographic characteristics. To better target interventions aimed at alcohol-related sexual risk behavior, our analyses simultaneously examine demographic predictors of both day-and event-level associations between alcohol consumption and sexual behavior in a sample of young adults (N = 301) who are sexually active and consume alcohol. Young adults (aged 18-29) recruited usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Women on average have reported consuming an average of three drinks before a hookup (Fielder and Carey, 2010b) or as many as five (LaBrie et al, 2014) whereas in the only study assessing men’s drinking level, the average was seven (LaBrie et al, 2014). Other event level research indicates that college students, especially those who are single or who report hooking up, are more likely to engage in sexual behaviors on days when they used more alcohol relative to those who were in casual or committed relationships (Patrick et al, 2015; Wells et al, 2016). However, as with global association studies, relationships between event-level alcohol and sexual behaviors are not entirely consistent.…”
Section: Alcohol and Hooking Upmentioning
confidence: 99%
“…Women on average have reported consuming an average of three drinks before a hookup (Fielder and Carey, 2010b) or as many as five (LaBrie et al, 2014) whereas in the only study assessing men’s drinking level, the average was seven (LaBrie et al, 2014). Other event level research indicates that college students, especially those who are single or who report hooking up, are more likely to engage in sexual behaviors on days when they used more alcohol relative to those who were in casual or committed relationships (Patrick et al, 2015; Wells et al, 2016). However, as with global association studies, relationships between event-level alcohol and sexual behaviors are not entirely consistent.…”
Section: Alcohol and Hooking Upmentioning
confidence: 99%
“…As noted, research has consistently demonstrated that illicit drug use is associated with sexual risk behavior (1719), but findings have been inconsistent for alcohol use (17, 18) and event-level studies typically do not find a significant association between alcohol use and sexual risk behavior (2124). Consistent with a previous event-level study (26), we found a positive association between alcohol use (in general and before sex) and CAS with casual partners, but not with serious partners.…”
Section: Discussionmentioning
confidence: 98%
“…There is some evidence that alcohol has a different effect on sexual behavior with casual versus serious partners, although findings have been mixed. In a sample of young adults (33% MSM), alcohol use had a stronger influence on sex among single people compared to partnered people (24). Additionally, an event-level study found a positive association between alcohol use before sex and CAS with casual partners, but not serious partners (26).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In 2017, Feinstein and Newcomb reported that same-day drinking among YMSM correlated with CAS with casual partners [ 25 ]. To date, no other studies with YMSM have replicated these findings, although same-day alcohol use has been found to be correlated with sexual behavior among YMSM [ 26 ]. Further, no studies in YMSM populations have used immediate event-level data of last sex for analysis.…”
Section: Introductionmentioning
confidence: 99%